OSG's Healing Cottage Design with a Cozy Retro Vintage Style - Dhifa, Nadhifa Syadira Surya (Bina Nusantara University, 2024)
In this era of modernization, many changes have been made to humanlifestyles.The effects of modernization have had many changing impacts, one ofwhich is the dominance of the use of foreign culture in the architectural andinterior fields, both in houses, cottages, hotels and other accomm odation. Thisresearch discusses the design of cottage interior designs related to foreign culturalissues that dominate in the era of modernization. By applying OSG's healincottageconcept with a cozy retro vintage style which aims to create a comfortable andcalming room atmosphere, this design uses the concept of a combination of Osingculture because it has a variety of aesthetics and cultures that are rarely found aswell as classic concepts such as retro vintage which supports an antique andelegant impression with a few gold accents applied in various corners of the room.This design uses materials that are soft and easy to care for. The aim of thisresearch is to maintain one's own cultural traditions, but not eliminate theelements of modernization and introduce Indonesian culture to citizens both athome and abroad.